How do molecular aberrations guide therapy in MDS?. Issue 4 (December 2021) - Bejar, Rafael
Abstract: Myelodysplastic syndromes (MDS) represent a cluster of genetically and phenotypically heterogeneous hematological disorders. While molecularly targeted therapies have entered the standard of care for other hematological malignancies like acute myeloid leukemia, this approach has been elusive in MDS. This review has summarized recent evidence to determine how molecular aberrations can be used to guide therapy in MDS and improve outcomes among patients.